Safety and security in the Malacca and Singapore Straits - Bateman, Sam (2016)
Shipping security in the Malacca and Singapore Straits has been much in the news during the past year. Due mainly to the existence of separatist groups and the high incidence of piracy in Southeast Asia, many observers believe that these strategically important waterways are at risk from a maritime terrorist attack. This situation has had unsatisfactory outcomes for the region, most notably the declaration by Lloyds of London that the Malacca Straits is a high war risk area for insurance purposes. This has meant increased insurance premiums for many vessels using the Straits.